Bandgap Engineering of an Aryl-Fused Tetrathianaphthalene for Visible-Blind Organic Field-Effect Transistors - Zhang, Lijuan; Tian, Xinzi; Sun, Yantao; Yao, Jiarong; Yang, Shuyuan; Liu, Zheyuan; Ge, Zhen; Zhang, Hongtao; Sun, Yan; Shao, Xiangfeng; Li, Rongjin; Hu, Wenping (Frontiers in Chemistry, 2021)
Stability problem of organic semiconductors (OSCs) because of photoabsorption has become a major barrier to their large scale applications in organic field-effect transistors (OFETs). It is imperative to design OSCs which are insensitive to visible and near-infrared (VNIR) light to obtain both environmental and operational stability. Herein, taking an aryl-fused tetrathianaphthalene (TTN2) as an example, we show that controlling molecular configuration is an effective strategy to tune the bandgaps of OSCs for highly stable OFETs. TTN2 adopts an armchair-like configuration, which is different from the prevailing planar structure of common OSCs. Because of the large bandgap, TTN2 exhibits no photoabsorption in the VNIR region and OFETs based on TTN2 show high environmental stability. The devices worked well after being stored in ambient air (i.e., in the presence of oxygen and water) and light for over two years. Moreover, the OFETs show no observable response to light irradiation from 405 nm to 1020 nm, which is also favorable for high operational stability.